Kritik Pemikiran Khalifah Hizbut Tahrir yang Autokratik - Ainur Rofiq Al Amin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
The proponents of Hizbut Tahrir (HT) claim that the structure of HT’s political system has been the sole best system, and it is deemed as a single compatible system to deal with all problems faced by the modern people in this modern age. The political system has been claimed as being capable of replacing all existing political systems in the world nowadays. They call this political system khilāfah coupled with khalīfah as the central elements. To the proponents of HT, the khilāfah system they promulgate among the Islamic communities throughout the world has been a legacy of the Prophet Muhammad. Therefore, the Muslim communities have to uphold this system regardless of their geographical boundaries. This article seeks to track roots of thought, which provide the political system called khilāfah and khalīfah propagated by HT foundation for its existence. In doing so, I will refer to authoritative references written and published by the proponents of HT. The study finds that the model of election, appointment, impeachment, and power of khalīfah along with obedience upon him, leads to autocratic governance.